Haematological malignancies in pregnancy: An overview with an emphasis on thrombotic risks - Horowitz, Netanel A.; Lavi, Noa; Nadir, Yona; Brenner, Benjamin (Thrombosis and Haemostasis, 2016)
With increase of maternal age, the incidence of haematological malignancies during pregnancy is rising and posing diagnostic and treatment challenges. Lymphoma is the fourth most common malignancy diagnosed in pregnancy; Hodgkin lymphoma is more frequent in pregnant women than non-Hodgkin lymphoma (NHL). The proportion of highly aggressive lymphomas in pregnant women is significantly higher than in non-pregnant women of reproductive age. Reproductive organ involvement is observed in almost half of pregnant women with NHL. The association of acute leukaemia and pregnancy is infrequent and it is assumed that pregnancy does not accelerate the disease course. Both cancer and pregnancy induce a procoagulant state which can lead to maternal venous thromboembolism (VTE) and placental occlusion. Pregnancy in woman with myeloproliferative neoplasms (MPN) promotes thrombotic environment, associating with an augmented risk of placental thrombosis, intrauterine growth retardation or loss and maternal thrombotic events.Haematological malignancies during pregnancy often require urgent diagnosis and management and are associated with potential adverse fetal outcomes. Most chemotherapeutic agents are teratogenic and should be avoided during the first trimester. Their use during the second and third trimesters may cause intrauterine growth restriction, premature birth and intrauterine fetal death. All chemotherapeutic drugs should be administered only after a detailed discussion with the patient and with close fetal monitoring. Chemotherapy and biological agents might also augment thrombotic risk. Guidelines for VTE prophylaxis in pregnant women with hematologic malignancies, apart from MPN, are currently unavailable, and therefore, clinical judgment should be made in each case.
Keywords: Haematological malignancy; pregnancy; hypercoagulability; venous thromboembolism; chemotherapy